User Registration Data for Strengthening Consumer Data Protection in Indonesian Digital MSMEs: A Malaysia Comparison - Hetharie, Yosia; Ikhwansyah, Isis; Rahmawati, Ema (Journal of Posthumanism, 2025)
The protection of consumers’ personal data is vital for the sustainability of digital MSMEs. Although Indonesia has Law No. 27 of 2022 on Personal Data Protection, the absence of mandatory data user registration creates gaps in supervision and compliance. This study analyzes the potential implementation of a data user registration system to strengthen personal data protection in Indonesia by comparing it with Malaysia, which has enforced such a system since 2013. This normative juridical study compares Indonesia’s PDPR and Malaysia’s PDPA to assess the role of data registration in MSME transparency and accountability. It finds that Malaysia’s data user registration system strengthens personal data protection through stricter oversight, while Indonesia’s lack of such a system may weaken supervision. The study recommends adopting a registration system in Indonesia to improve compliance, transparency, and data security for digital MSMEs.